2006
DOI: 10.1557/proc-932-28.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Stress Corrosion Cracking (ASCC) Susceptibility of Stainless Alloys for Metallic Containers

Abstract: Metallic canisters placed in concrete casks and containing spent nuclear fuel elements, will be exposed to a moist oceanic atmosphere while the decay heat generated in the fuel elements cools for more than fifty years. Thus, the surface environment of the metallic canisters will be wet and covered with chloride compounds. The canisters may suffer atmospheric stress corrosion cracking. Therefore, corrosion tests for some potential alloys were conducted in an aqueous bittern solution, containing 22% enriched chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Should sufficient tensile stress be present, there is ample evidence that these stainless steels are susceptible to chloride-induced SCC (CISCC) in aggressive chloride-bearing environments. SCC of 304 stainless steel (SS), the most widely used alloy for containers that are currently in service, occurs readily in experimental tests with deliquesced sea-salts (e.g., Nakayama 2006;Prosek et al 2009;Tani et al 2009;Mintz et al 2012;Prosek et al 2014), and has also been observed in near-marine ambient temperature field tests and industrial sites (Kain 1990;Hayashibara et al 2008;Kosaki 2008;Cook et al 2011;Nakayama and Sakakibara 2013;Cook et al 2014). However, overall susceptibility is a function of several factors, including the degree of sensitization, the degree of cold work, and the surface finish (Parrott and Pitts 2011); to date, none of these factors have been assessed for materials representative of fielded interim storage canisters.…”
Section: Susceptible Materialmentioning
confidence: 99%
“…Should sufficient tensile stress be present, there is ample evidence that these stainless steels are susceptible to chloride-induced SCC (CISCC) in aggressive chloride-bearing environments. SCC of 304 stainless steel (SS), the most widely used alloy for containers that are currently in service, occurs readily in experimental tests with deliquesced sea-salts (e.g., Nakayama 2006;Prosek et al 2009;Tani et al 2009;Mintz et al 2012;Prosek et al 2014), and has also been observed in near-marine ambient temperature field tests and industrial sites (Kain 1990;Hayashibara et al 2008;Kosaki 2008;Cook et al 2011;Nakayama and Sakakibara 2013;Cook et al 2014). However, overall susceptibility is a function of several factors, including the degree of sensitization, the degree of cold work, and the surface finish (Parrott and Pitts 2011); to date, none of these factors have been assessed for materials representative of fielded interim storage canisters.…”
Section: Susceptible Materialmentioning
confidence: 99%
“…SCC of 304/316 stainless steel has been observed in near-marine ambient temperature field tests and industrial sites (Kain 1990, Hayashibara et al 2008, Kosaki 2008, Nakayama and Sakakibara 2013, Cook et al 2014. In elevated-temperature experimental tests with deliquesced sea-salts that were meant to replicate conditions on the surface of an SNF interim dry storage canister, SCC has been shown to occur readily in both base metal and weld specimens (e.g., Nakayama 2006, Prosek et al 2009, Tani et al 2009, Mintz et al 2012, Prosek et al 2014.…”
Section: Materials Susceptibilitymentioning
confidence: 99%
“…The pits grow over time, and once they reach a sufficient depth (generally around 70-100 µm, but this is a function of the tensile stresses present), they serve as initiation loci for SCC. Experimental studies have shown that SCC commonly originates at corrosion pits (e.g., Kondo 1989, Turnbull and Zhou 2004, Nakayama 2006, Turnbull et al 2006b, Turnbull et al 2006a, Kosaki 2008, Prosek et al 2009, Albores-Silva et al 2011, Shirai et al 2011. Pit growth rates are poorly understood; at ambient temperatures, pit growth may be quite slow (e.g., Chen and Kelly 2010), and SCC initiation may take several years.…”
Section: Scc Initiationmentioning
confidence: 99%
“…In combination with anticipated high weld residual stresses (NRC 2013) and potential sensitization in the HAZ, SCC may be possible. Several experimental studies (e.g., Nakayama 2006;Tani et al 2009Tani et al , 2010Mintz et al 2012;Prosek et al 2009Prosek et al , 2014NRC 2014) have observed SCC under conditions nominally typical of the surface of interim storage canisters stored at near-marine Independent Spent Fuel Storage Locations (ISFSIs).…”
Section: Canister Shellmentioning
confidence: 99%
“…SCC of welded zones is of special concern, as it a well-documented mode of attack for austenitic stainless steels (including 304 and 316 SS) in marine environments (Kain 1990). Several experimental studies (e.g., Nakayama 2006;Tani et al 2009Tani et al , 2010Mintz et al 2012;Prosek et al 2009Prosek et al , 2014NRC 2014) have observed SCC under conditions nominally expected to occur on the surfaces of canisters stored near bodies of salt water.…”
Section: Interim Storage Environmentmentioning
confidence: 99%